2012
DOI: 10.1007/s10059-012-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased Polyamine Biosynthesis Enhances Stress Tolerance by Preventing the Accumulation of Reactive Oxygen Species: T-DNA Mutational Analysis of Oryza sativa Lysine Decarboxylase-like Protein 1

Abstract: A highly oxidative stress-tolerant japonica rice line was isolated by T-DNA insertion mutation followed by screening in the presence of 50 mM H 2 O 2 . The T-DNA insertion was mapped to locus Os09g0547500, the gene product of which was annotated as lysine decarboxylase-like protein (GenBank accession No. AK062595). We termed this gene OsLDC-like 1, for Oryza sativa lysine decarboxylase-like 1. The insertion site was in the second exon and resulted in a 27 amino acid N-terminal deletion. Despite this defect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 48 publications
(50 reference statements)
3
32
0
Order By: Relevance
“…NADPH oxidase is the key enzyme catalyzing the production of O • 2 − (Kaur et al ., ). We then monitored the mRNA amounts of three NADPH oxidase genes, RbohB (Nagano et al ., ), RbohD and RbohF (Jang et al ., ). Guy11 infection clearly decreased their RNA amounts in all three WT rice varieties – Kasalath, NPB and TP309.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…NADPH oxidase is the key enzyme catalyzing the production of O • 2 − (Kaur et al ., ). We then monitored the mRNA amounts of three NADPH oxidase genes, RbohB (Nagano et al ., ), RbohD and RbohF (Jang et al ., ). Guy11 infection clearly decreased their RNA amounts in all three WT rice varieties – Kasalath, NPB and TP309.…”
Section: Resultsmentioning
confidence: 97%
“…In Arabidopsis, both RbohD and RbohF are required for ROS production, as atrbohD and atrbohF mutants show lower ROS concentrations during incompatible interactions with bacterial and oomycete pathogens (Torres et al, 2002). In rice, RbohD and RbohF are induced by oxidative stress, leading to increased intracellular ROS accumulation (Jang et al, 2012). RbohB knockdown rice plants display enhanced susceptibility to rice blast fungus Magnaporthe oryzae, suggesting that RbohB is required for resistance to rice blast (Nagano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al . () found that the osldc like‐1 rice mutant line had a higher tolerance to abiotic stress by preventing the accumulation of ROS. Additionally, the mutant lines PAs accumulations were significantly increased, showing that increased endogenous PAs biosynthesis was an effective strategy to enhance crops tolerance to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they can preserve the thylakoid membranes integrity and function under stress condition [50]. On the other hand, this stabilization may be due to the antioxidant character of Spm [51][52][53]. Indeed, the presence of the tetra-amine at or near the site of ROSs generation (FA and FB located on PsaC) likely favoured the ROSs scavenging before they damage the PSI polypeptides.…”
Section: Discussionmentioning
confidence: 92%